2015
DOI: 10.1093/cid/civ536
|View full text |Cite
|
Sign up to set email alerts
|

Telavancin Hospital-Acquired Pneumonia Trials: Impact of Gram-Negative Infections and Inadequate Gram-Negative Coverage on Clinical Efficacy and All-Cause Mortality

Abstract: In the ATTAIN safety population there were 16 more deaths in the telavancin arms than in the vancomycin arms. Of these, 13 were in patients with gram-negative-only infections (n = 9) or with mixed infections and inadequate GNC (n = 4) and all had estimated baseline creatinine clearances of <30ml/min. Based on this analysis, clinical response and all-cause mortality could be confounded because there were more patients with gram-negative pathogens at baseline and more patients received inadequate treatment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…At present, black box warnings are issued for telavancin regarding nephrotoxicity and increased mortality in patients with preexisting moderate/severe impaired kidney function (creatinine clearance ,50 ml/min) who are being treated for hospital-acquired or ventilatorassociated bacterial pneumonia (34). A post hoc analysis of the Assessment of Telavancin for Treatment of Hospital-Acquired Pneumonia (ATTAIN) trials suggests that the increased mortality in this patient population may have been related to a greater number of patients with Gramnegative organisms at baseline in the telavancin groups and by inadequate treatment of these Gram-negative organisms (36). Furthermore, in patients with severe kidney dysfunction or requiring hemodialysis, it has been demonstrated that telavancin's biologic activity against S. aureus is maintained (37).…”
Section: Lipoglycopeptidesmentioning
confidence: 99%
“…At present, black box warnings are issued for telavancin regarding nephrotoxicity and increased mortality in patients with preexisting moderate/severe impaired kidney function (creatinine clearance ,50 ml/min) who are being treated for hospital-acquired or ventilatorassociated bacterial pneumonia (34). A post hoc analysis of the Assessment of Telavancin for Treatment of Hospital-Acquired Pneumonia (ATTAIN) trials suggests that the increased mortality in this patient population may have been related to a greater number of patients with Gramnegative organisms at baseline in the telavancin groups and by inadequate treatment of these Gram-negative organisms (36). Furthermore, in patients with severe kidney dysfunction or requiring hemodialysis, it has been demonstrated that telavancin's biologic activity against S. aureus is maintained (37).…”
Section: Lipoglycopeptidesmentioning
confidence: 99%
“…Appropriate initial antibiotic therapy has been demonstrated as the key independent factor of treatment outcomes in patients with Gram-negative bacteremia in several previous studies [11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…Appropriate initial antibiotic therapy has been demonstrated as the key independent factor of treatment outcomes in patients with Gram-negative bacteremia in previous studies from the adult ICUs or wards [11][12][13][14]. However, this issue has not been fully studied in the NICU, except for a small sample size, case-control study found in the literature [15].…”
Section: Introductionmentioning
confidence: 99%